Portrait of Friedrich Gottlieb Klopstock - Adé, Jakob Julius, b. 1828 (engraver):::Creator::::::::::::; Juel, Jens, 1745-1802 (artist):::Contributor::::::::::::
Portrait of Friedrich Gottlieb Klopstock possibly based on painting of Klopstock by Jens Juel.